Atividades exploratório-investigativas em sala de aula de cálculo I com uso de tecnologia - Carvalho, Diana Vieira de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This study presents the results from a qualitative resource, based on research-action methodology, which examined the innovate teaching practices implementations in the Calculus I during 2011 year. The analysis of collected data from three used sources – an initial questionnaire, an exploratory-investigative classroom, and an interview with some students at the end of the second semester – reveals that the students had appropriated of the technological recourses, using it as a tool to look for the knowledge. The investigative activities with the use of information technologies made the use of multiple representations in solving mathematical tasks, making the transition of numerical, algebraic and geometrical results possible for the students when they have looking for validation of their hypotheses and conjectures during mathematical problems solving. This works helped in the insertion of new practices in the discipline, and their results validate the proposal presented by the teacher, which is the discipline of Calculus use, whose character is strongly linked to the training content of the student, as a discipline whose can contributed to the pedagogical formation of the graduation student, leading him to know the Mathematical Education possibilities, specially the Mathematical Investigation - Solving Problems, in the outlook of dialogued classes where the teacher assumes the facilitator role and where the students become actives in their pursuit of knowledge

Este trabalho apresenta os resultados de uma pesquisa qualitativa, na modalidade pesquisa-ação, que analisou a implantação de práticas pedagógicas inovadoras na disciplina de Cálculo I no ano de 2011. A análise dos dados coletados em três fontes utilizadas - um questionário inicial, uma aula exploratório-investigativa, e uma entrevista realizada com alguns alunos no fim do segundo semestre letivo – revela que os alunos se apropriaram do recurso tecnológico, usando-o como uma ferramenta na busca do conhecimento. As atividades investigativas com o uso de tecnologias informáticas possibilitaram a construção de representações múltiplas na resolução de tarefas matemáticas, fazendo com que os alunos transitassem pelos resultados numéricos, algébricos e geométricos na busca da validação das suas conjecturas durante a resolução de problemas matemáticos. A pesquisa auxiliou na inserção de novas práticas na disciplina, e seus resultados validam a proposta apresentada pela professora: usar a disciplina de Cálculo, cujo caráter é fortemente ligado à formação conteúdista do aluno, como uma disciplina onde é possível contribuir para a formação pedagógica do aluno de Licenciatura, levando-o a conhecer possibilidades da pesquisa em Educação Matemática na modalidade Investigação Matemática - Resolução de Problemas, na busca de aulas dialogadas, onde o professor assume o papel de mediador e o aluno se torna ativo na busca do seu conhecimento
Keywords: Matemática - Estudo e ensino; Cálculo; Tecnologia da informação; Pratica de ensino; Teaching Cauculus; Mathematical Investigation; Information Technologies